The Utilization of Para‐Substituted Triphenylphosphine Derivatives to Synthesize Highly Emissive Cyclometalated Platinum(II) Complexes. Issue 46 (29th November 2021) - Shahsavari, Hamid R.; Chamyani, Samira; Hu, Jiyun; Aghakhanpour, Reza Babadi; Rheingold, Arnold L.; Paziresh, Sareh; Rahal, Dania; Tsuji, Miu; Momand, Bilal; Beyzavi, Hudson
Abstract: Herein, the synthesis and characterization of a series of heteroleptic cycloplatinated(II) complexes [Pt( p ‐MeC6 H4 )(dfppy)(L)], dfppy=2‐(2, 4‐difluorophenyl)pyridinate), with different para ‐substituted triphenylphosphine ligands (L) are reported. The complexes exhibit greenish‐blue phosphorescence under UV light at room temperature in their solid states. Their emissions appear as structured bands which indicates that the emissions mainly originate from the electronic transitions in the dfppy ligand with small contribution of metal to ligand and/or ligand to ligand charge transfers. The phosphine ligands do not have a considerable impact on the shape and wavelength of the emissions. However, the electron density of the phosphine ligands affects the emission strengths significantly. To rationalize the experimental photophysical data, density functional theory (DFT) and time‐dependent DFT (TD‐DFT) calculations were employed for all the complexes. Abstract : Combining a fluorinated C^N cyclometalating ligand with various para ‐substituted triphenylphosphine ligands provides cycloplatinated(II) complexes as bright greenish‐blue emitters in different conditions.